Износо- и коррозионностойкие сплавы на основе кобальта для наплавки - By, Дж.Б.С.; Павленко, А.В. (Автоматическая сварка, 2004)
Описаны особенности структуры свойств износо- и коррозионностойких наплавочных сплавов на основе кобальта с различным типом упрочнения. Кратко отмечены способы их нанесения на изделия. Даны примеры промышленного применения сплавов. Cobalt-based alloys for resisting wear and corrosion were first developed prior to 1907 under the trademark Stellite(r). Additional alloys were later developed for needs in a variety of applications. Cobalt alloys can be applied on the surface of industrial components by hardfacing or thermal spraying. This paper is intended to review the traditional, as well as recently developed cobalt alloys in regards to their metallurgical characteristics and industrial applications. Various technologies for surfacing are discussed. Examples of using cobalt alloys in various industries for surfacing are illustrated in this work.